UJI DOSIS DAN CARA APLIKASI BIOFUNGISIDA Bacillus sp. TERHADAP PENYAKIT JAMUR AKAR PUTIH (Rigidoporus lignosus) PADA TANAMAN KARET DI PEMBIBITAN - Benny Benny; Lahmuddin Lubis; Syahrial Oemry (Universitas Sumatera Utara, 2013)
Dose Test and Application Ways Biofungiside Bacillus sp. Against White Root Fungi(Rigidoporus lignosus) on Rubber of Plants in the Nursery. This study aims to determine the effectof dose and ways application biofungiside with of Bacillus sp. against white root fungi(Rigidoporus lignosus) on rubber of plants in the nursery, as well as determine the effect of thewhite root fungi disease on the bud tall of rubber stump. The research was conducted usingRandomized Block Design (RAK) factorial consisting of two factors and 4 replications. The firstfactor, namely P0: control, P1: 20ml/1 liter water, P2: 30ml/1 liter water, P3: 40ml/1 liter water andthe second factor A1 (spraying) and A2 (deeping). The result showed the dose treatment containedthe highest intencity of the attacks on the P0 of 88,54% and lowest in P3 at 20,83%. Waysapplication treatment intensity of the attacks on the A1 of 35,94% and A2 at 54,69%. Interactionsof dose and ways application of the highest intensity of attacks are on P0A2 of 89,59% and lowestin P3A1 at 6,25%. The highest bud tall on dose treatments contained in P3 of 17,78 cm, the lowestin the P0 of 3,52 cm. Ways application treatment in A1 of 14,78 cm and A2 of 9,87 cm.Interactions in the bud tall of dose and ways application was highest in P3A1 of 21,04 cm, thelowest in P0A2 of 3,00 cm.